The Appeal of a Radical Theology of Peace Thomas Merton – Pacem in Terris – Pope Francis - Sengers, Erik (Asian Horizons, 2023)
The standpoint of the Vatican on the war in Ukraine, pointing to the victims on both sides of the front and demanding an end to the fights, irritates international diplomacy. This article wants to show that this position is grounded in Pacem in Terris and Gaudium and Spes and may have been informed by US Trappist monk Thomas Merton. In the second part, a summary of his pamphlet Peace in the post-Christian Era is given. In the third part, the Vatican Documents of 1963 and 1965 are summarized. In the fourth part, a sketch of Pope Francis’ peace theology is made. In the conclusions, the continuities and innovations of this radical peace theology are indicated. Adapted to the conflicts of our time, this theology confronts us with the tragedies of war and portrays a vision of peace that invites us to change our behaviour and mindset.